PROBLEM ASPECTS OF LEGAL REGULATION AIR TRANSPORTATION IN UKRAINE - Zhmur, Nataliia; Yemets, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to research and analyze the current legislation on the regulation of air transportation and how the military conflict affected the indicators of air transportation in Ukraine. Research methods: in order to achieve the defined goal and set tasks, empirical research methods were used, such as a comparison of the dynamics of air transport and the aviation sector in Ukraine during the conflict period, measuring the number of passengers using air transport services in Ukraine. and observation of changes in the volume of passenger and cargo air transportation in Ukraine at various stages of the conflict, as well as theoretical research methods, such as the analysis of statistical data on the volume of passenger and cargo transportation, the activities of airlines and airports in Ukraine during the Russian-Ukrainian conflict. Also, the multifacetedness of the research subject is due to the use of both general scientific and private scientific methods. Results: both national and international legislation on air transportation has been analyzed and researched, and allows us to state that such transportation is carried out in accordance with the provisions of international legal acts and national legislation regulating air transportation; the current state and development trends of the aviation industry of Ukraine in the period from 2014 to 2022 were analyzed; an assessment of changes in the volume of cargo transportation by air transport and passenger air transportation through airports was made, the consequences of the impact of the war on air transportation in Ukraine were summarized; a comparative analysis of air transport in Ukraine with other countries was carried out; an analysis of the measures adopted to ensure the safety of air transport in the conditions of the Russian-Ukrainian conflict was carried out; the main risk factors that can affect the safety of air flights in the conditions of armed aggression were identified, and proposals for possible measures to restore the aviation sector were also analyzed. Discussion: an analysis of regulatory legal acts regulating air transportation was carried out, and it was found that the regulatory framework meets the requirements of proper and safe transportation; an analysis of losses suffered by airlines, airports and aviation infrastructure as a result of the war was carried out.